2020
DOI: 10.1021/acs.jpclett.0c01411
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Observation of Surface-Enhanced Coherent Raman Scattering with 105–106 Enhancement

Abstract: Combining surface-enhanced Raman scattering (SERS) with the coherent nonlinear Raman technique is a promising route for achieving higher sensitivity and time-resolved SERS measurements, yet such attempts have just been started. Here, we report time-domain Raman measurements of trans-1,2-bis­(4-pyridyl)­ethylene (BPE) adsorbed on gold nanoparticle assemblies (GNAs), which were carried out with impulsive stimulated Raman spectroscopy using sub-8 fs pulses. We observe coherent nuclear wavepacket motion of BPE on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…TR-SE-ISRS will also be a powerful tool to study plasmon-induced photochemical reactions, which have been attracting extensive attention although their mechanisms have been controversial . In this direction, we recently reported time-domain measurements of surface-enhanced Raman signals and demonstrated that surface-enhanced ISRS (SE-ISRS) can achieve an enhancement factor as high as 10 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TR-SE-ISRS will also be a powerful tool to study plasmon-induced photochemical reactions, which have been attracting extensive attention although their mechanisms have been controversial . In this direction, we recently reported time-domain measurements of surface-enhanced Raman signals and demonstrated that surface-enhanced ISRS (SE-ISRS) can achieve an enhancement factor as high as 10 6 …”
Section: Discussionmentioning
confidence: 99%
“…138 In this direction, we recently reported time-domain measurements of surfaceenhanced Raman signals and demonstrated that surfaceenhanced ISRS (SE-ISRS) can achieve an enhancement factor as high as 10 6 . 139 Extending TR-ISRS to multi-dimensional spectroscopy is another exciting direction. In TR-ISRS, the actinic pump pulse is used primarily to populate the excited state.…”
mentioning
confidence: 99%
“…(c) Fourier transform power spectra of the oscillatory components shown in the inset of (b). Adapted from ref . Copyright 2020 American Chemical Society.…”
Section: Sers Substrate In 4d Space and Time Domainsmentioning
confidence: 99%
“…213 In fact, the work combining SERS and coherent nonlinear time-resolved Raman spectroscopy has been reported. Kumar et al 214 combined surfaceenhanced Raman scattering with the coherent nonlinear Raman technique and made it a promising route for achieving higher sensitivity and time-resolved SERS measurements. They also reported time domain Raman measurements of trans-1,2bis(4-pyridyl)ethylene (BPE) adsorbed on Au nanoparticle assemblies, which are carried out with impulsive stimulated Raman spectroscopy using sub-8 fs pulses (Figure 12a).…”
Section: Femtosecond Temporal Resolutionmentioning
confidence: 99%
“…Surfaceenhanced CRS was first demonstrated in 1979 where the coherent anti-Stokes Raman scattering (CARS) signal from liquid benzene was amplified with the help of surface plasmon polaritons supported on a flat Ag film antenna [12]. Subsequent progress on surface-enhanced CRS has focused largely on engineering metallic nanoantennas based on Au and Ag to increase and/or optimize the sensitivity of detection [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The quest has seen considerable success and single-molecule sensitivity has been demonstrated by multiple groups [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%